Analisis Pemanfaatan Peta Konsep dalam Meningkatkan Kemampuan Berpikir Kreatif Kelas XI IPS 2 Materi Ketenagakerjaan SMA Negeri 11 Kota Jambi - Sonia Kurnia Putri; Pratiwi Indah Sari (SJEE (Scientific Journals of Economic Education), 2023)
This study aims to determine the use of concept maps in improving the creative thinking skills ofstudents of class XI IPS 2 at SMA Negeri 11 Jambi City. This type of research uses qualitative research.Meanwhile, the technique in this research uses the cluster sampling technique to determine when the object tobe researched or the data source is very extensive. The research results show that optimal learning activitiesmust have the right strategy, one of which is using concept maps. Because, this greatly influences studentsthinking abilities, so they are able to solve the problems given. Thus, the use of concept maps to presentinformation in the form of related concepts so that with the help of these concept maps can foster a moremeaningful learning process. Thus students can develop their creative thinking by remembering the importantinformation obtained.